2021
DOI: 10.1007/s43032-021-00643-x
|View full text |Cite
|
Sign up to set email alerts
|

Low Anti-Mullerian Hormone Levels Are Associated with the Severity of Anxiety Experienced by Healthcare Professionals During the COVID-19 Pandemic

Abstract: The objective of this study is to investigate a possible correlation between anxiety status and anti-Mullerian hormone (AMH) levels among healthcare professionals who provide medical care directly to COVID-19-positive patients during the recent pandemic. Fifty-two healthcare professionals (nurses, midwives, and residents) who provide medical care directly to COVID-19-positive patients in inpatient clinics or intensive care units were enrolled in this study. Serum AMH levels were analyzed to reflect ovarian res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 25 publications
(38 reference statements)
0
6
0
Order By: Relevance
“…In addition, recent studies were reported that, low serum AMH levels were associated with psychological stress and severity of anxiety (Yeğin et al, 2021). Menstruation, which is arranged by the HPO axis, may be easily disarranged by psychological stress, infection disease, drugs and organ dysfunctions (Yeğin et al, 2021, Kala et al, 2016.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, recent studies were reported that, low serum AMH levels were associated with psychological stress and severity of anxiety (Yeğin et al, 2021). Menstruation, which is arranged by the HPO axis, may be easily disarranged by psychological stress, infection disease, drugs and organ dysfunctions (Yeğin et al, 2021, Kala et al, 2016.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, recent studies were reported that, low serum AMH levels were associated with psychological stress and severity of anxiety (Yeğin et al, 2021). Menstruation, which is arranged by the HPO axis, may be easily disarranged by psychological stress, infection disease, drugs and organ dysfunctions (Yeğin et al, 2021, Kala et al, 2016. Appropriately, in our study results, it was found that the number of women with irregular menstruation and amenorrhea slightly increased after COVID-19 illness; however, the study patients had a significant reduction in menstrual volume during 3 months following illness.…”
Section: Discussionmentioning
confidence: 99%
“…For infertile women who recovered from COVID‐19, the present finding could provide real‐world evidence for their medical consultations on subsequent ART success. Since these women are often confronted with higher levels of anxiety and depression, 46 our reassuring data may also help to reduce the psychiatric stress and further protect them from potential negative consequences 47–49 . Of note, this study did not preclude the importance of timely COVID‐19 vaccination, which has shown its effectiveness in reducing morbidity and mortality as well as safety for assisted reproductive outcomes 50,51 …”
Section: Discussionmentioning
confidence: 91%
“…Low serum levels of AMH have also been connected to psychological stress and anxiety intensity. Additionally, low plasma AMH measures were also related to emotional stress and the severity of anxiety [48]. Therefore, psychological counseling should always be offered especially during this difficult period of the pandemic.…”
Section: Psychological Impact On Art During the Pandemicmentioning
confidence: 99%